Developing al-Siyasah al-Shar'iyyah Framework for Contemporary Public Policy Analysis - Mustafa Omar Mohammed; Omar Kachkar (Media Syari'ah, 2017)
Al-Siyasah al-Shar'iyyah (SS) in Islamic history had played significant role in guiding and regulating the relations, activities and policies of Muslim states towards meeting Maqasid al-Shari'ah. Over time, this science became conservative and overloaded with general Shari'ah rules, and thus deficient of establishing a robust system of public policy formulation and analysis comparable to the current well developed conventional public policy system. Most of the literatures on al-Siyasah al-Shar'iyyah, past and present, still discuss the subject within the general principles of the Shari'ah. The present paper adopts content and thematic analyses to develop SS theoretical framework. It has used the new framework to present policy cases in Islamic Turath scientifically. Once refined, the new SS framework can be used for contemporary public policy analysis from Islamic perspective. The paper has set new direction for presenting SS scientifically that suits contemporary public policy analysis.